Address: Thoughts on Restructuring Government - Allen Weinstein; Charles Robb (Washington University Law Quarterly, 1990)
Chuck will speak this morning on "random constitutional thoughts with some particular bellyaching about the budget process." Without further comment I present to you the co-chairman of this conference, Senator Charles S. Robb.